The Role of Business Sustainability in Human Resource Management: A Study on Indian Manufacturing Companies - R., Vasantha Lakshmi; Kennedy, Dr. Hanuman (The South East Asian Journal of Management, 2017)
Business sustainability from the point of view of human resource management (HRM) is a management and leadership philosophy about how people are most enable to contribute to success at their work by minimizing the negative impact of their work on the environmental and social factors and at the same time improving the financial factors in the organizations. This study is an empirical study conducted on 233 Indian manufacturing firms operating in the Karnataka region to investigate the role for HRM in business sustainability. The role for HRM in business sustainability is studied with the construct HRM strategic integration in business sustainability strategy. Further, this study focuses on the way HRM incorporates sustainability in its practices in the organization and its impact on the organizational performance. The data are analyzed using SEM, and the results revealed the significance of the relationship of the HRM strategic integration of sustainability strategy with the organizational performance. The organizational performance studied with respect to the three factors of business sustainability viz., profit, people, and planet. Further, these relationships are tested with contingency factors, age of the firm, and the number of employees for its significance in this relation. The empirical evidence of the study shows a significant positive relation of organizational performance when HRM has strategic integration in business sustainability strategy. Model I4C is derived to show the role for HRM in business sustainability.